2003
DOI: 10.1210/jc.2002-021267
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Regional Fat Distribution, and Syndrome X in Obese BlackVersusWhite Adolescents: Race Differential in Diabetogenic and Atherogenic Risk Factors

Abstract: The incidence of type 2 diabetes mellitus in children is increasing with the increasing prevalence of obesity, particularly in African-American children. We hypothesized that African-American obese adolescents are more insulin resistant than their white peers, but have lower insulin secretion, thus increasing their risk of type 2 diabetes mellitus. The present study investigated insulin sensitivity and secretion, visceral adiposity (VAT), and cardiovascular disease (CVD) risk profile in black obese adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
226
2
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(263 citation statements)
references
References 47 publications
21
226
2
4
Order By: Relevance
“…It is likely that these ranges will need to be assay and population specific. 36,37 We agree with Lambert et al that the insulin resistance syndrome (IRS) of childhood, or pre-MS, may be a better name than MS in this age group.…”
Section: Discussionsupporting
confidence: 84%
“…It is likely that these ranges will need to be assay and population specific. 36,37 We agree with Lambert et al that the insulin resistance syndrome (IRS) of childhood, or pre-MS, may be a better name than MS in this age group.…”
Section: Discussionsupporting
confidence: 84%
“…Abdominal adiposity is associated with numerous health risk in the pediatric (Bacha et al, 2003;Weiss et al, 2003) and adult populations (Ross et al, 2002;Hayashi et al, 2004). In adults, emerging evidence suggests that cardiorespiratory fitness (CRF) is associated with lower visceral and abdominal subcutaneous adipose tissue (AT) Janssen et al, 2004) independent of body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…In that study (Nassis et al, 2005), total and abdominal fat was estimated by sum of skinfolds and CRF was indirectly assessed by 20 m shuttle run test. It is currently unknown whether CRF is associated with visceral AT, a strong independent predictor of insulin resistance and type 2 diabetes in youth (Bacha et al, 2003;Weiss et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been reported racial differences in regional fat distribution, intra-abdominal and subcutaneous abdominal adipose tissue patterns and metabolism (Berman et al, 2001;Raji et al, 2001;Weinsier et al, 2001;Bacha et al, 2003). Further examinations considering other populations will be required.…”
Section: Discussionmentioning
confidence: 96%